Invisible trillions : how financial secrecy is imperiling capitalism and democracy--and the way to renew our broken system - Baker, Raymond W., 1935- (Berrett-Koehler Publishers, Inc., 2023)
"Our current democratic capitalist system is close to imploding. This book is the first to reveal the secret financial system dominating capitalism today and shows how we can create accountability to restore our democracy. Over the last half century, capitalism has created the means for trillions of dollars, euros, pounds, and other stores of wealth to move invisibly-beyond the control of central bankers, law enforcement agents, and international institutions. With an entire financial secrecy system now dominating capitalist operations, riches move inexorably upward and accelerate economic inequality, directly obstructing and threatening democracy. In three parts, Invisible Trillions reveals how capitalism today functions outside the control of democracy and how we can link the two once again. Acknowledging the corruption and complacency of our institutions, Raymond W. Baker walks readers through covert financial operations, their instigators, and their impacts. He also argues for replacing financial secrecy with transparency via mechanisms such as mandated disclosure around corporate and financial entities and operations. This book takes the first step toward holding our systems accountable. After all, the very survival of the democratic capitalist system is at stake"--